Development of community-based coffee agrotourism in West Nusa Tenggara province - Aida Muspiah; Intan Taufik; Amrullah (Yayasan Siti Widhatul Faeha, 2025)
Sustainable rural development requires strategies that optimise local resources while maintaining environmental and socio-cultural sustainability. The purpose of this study is to analyze the development of community-based coffee agrotourism in East Lombok Regency, West Nusa Tenggara Province, as a strategy to strengthen sustainable rural economic development. The research method uses a qualitative descriptive approach from secondary data to analyze the biophysical potential of local coffee-based agroecosystems, the institutional readiness of farmer groups and regional organizations, and existing collaboration mechanisms between government, communities, academics, and private actors. The results indicate that East Lombok has the potential to be developed into coffee agrotourism based on its natural and socio-cultural conditions, agricultural climate, farming communities, and local traditions. Obstacles faced include tourism infrastructure, community management capacity, and weak coordination between institutions. The recommended model to overcome the difficulties of agrotourism development is Community-Based Tourism (CBT), which integrates economic, socio-cultural, and ecological dimensions. In addition, cross-sector collaboration (quadruple helix) is needed to ensure a stable distribution of economic and environmental benefits. Therefore, the results of this study provide a practical basis for planning and policy-making related to the development of inclusive and sustainable agrotourism.